2015
DOI: 10.33151/ajp.12.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Mass gathering medical planning: An overview of the Australian Surf Life Saving Championships

Abstract: The Australian Surf Life Saving Championships (the ‘Aussies’) were held between 31 March and 6 April 2014, at Scarborough Beach in Western Australia. The event attracted 6,000 persons including competitors, support staff and officials. It is estimated that 70,000 spectators attended the event over the seven days of competition.This article provides an overview of the Aussies, outlines its medical planning and role of the medical team, and describes the team structure. Equipment and team deployment is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[ 7 ] Zeitz et al[ 27 ] found a significant relationship between maximum daily temperature and patient applications. [ 28 ] In the research conducted in Singapore Formula 1 Races (2009–2012), no relationship between the temperature and PPR was found. [ 22 ] It is similar to the results of this research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Zeitz et al[ 27 ] found a significant relationship between maximum daily temperature and patient applications. [ 28 ] In the research conducted in Singapore Formula 1 Races (2009–2012), no relationship between the temperature and PPR was found. [ 22 ] It is similar to the results of this research.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, care has been taken to ensure that medical services are adequate at most confined mass gatherings (Reid et al , 2015); however, the sheer size of a major event such as the GC2018 also stretched well into major transport issues and had far-reaching effects, ranging from the Brisbane City region to the widespread Gold Coast venues. Traffic congestion was a major concern and risk for emergency services agencies.…”
Section: Major Event Safety and Transport Planningmentioning
confidence: 99%